2009
DOI: 10.1016/j.eurpsy.2009.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Do community mental health teams caring for severely mentally ill patients adjust treatments and services based on patients’ antisocial or criminal behaviours?

Abstract: While the frequency of meetings with CMHTs increased with the severity of antisocial behaviours, no specific treatments were provided to patients with SMI engaging in antisocial behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…Unfortunately, the studies we identified here lacked information regarding such aetiological heterogeneity, and whether specific interventions were provided to reduce aggression. However, the limited literature in this area suggests that patients with severe mental illness (SMI), engaging in antisocial behaviour, do not receive specific treatments to target their antisocial behaviour .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the studies we identified here lacked information regarding such aetiological heterogeneity, and whether specific interventions were provided to reduce aggression. However, the limited literature in this area suggests that patients with severe mental illness (SMI), engaging in antisocial behaviour, do not receive specific treatments to target their antisocial behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high rates of aggressive behaviour have been reported both within community and inpatient mental health settings. Further, recent reviews have highlighted concerns that current treatments for psychosis are not successful in reducing associated aggressive behaviours; an observation supported by empirical findings . Nevertheless, there are no reviews which systematically compare rates of aggression during FEP prior to, and following, service contact.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the civil liberties issues raised by AOT, recent studies conclude that it reduces suicide attempts and physical harm to self, abuse of alcohol or drugs, physical harm to others, damaged or destroyed property, threatened physical harm to others, arrests, and gun violence (Gilbert et al, 2010;Phelan, Sinkewicz, Castille, Huz, & Link, 2010;Swartz & Swanson, 2004). In contrast, treatment programs such as Assertive Community Teams (ACT) and Intensive Care Management (ICM) teams do not reduce incarceration rates (Hodgins et al, 2009). However, when care focuses simultaneously on psychosis and antisocial behavior, as is the case with Forensic Assertive Community Teams (FACT), reductions in antisocial behaviors are evident (Hodgins et al, 2009).…”
Section: Treatment Implicationsmentioning
confidence: 91%
“…In contrast, treatment programs such as Assertive Community Teams (ACT) and Intensive Care Management (ICM) teams do not reduce incarceration rates (Hodgins et al, 2009). However, when care focuses simultaneously on psychosis and antisocial behavior, as is the case with Forensic Assertive Community Teams (FACT), reductions in antisocial behaviors are evident (Hodgins et al, 2009). FACT teams, which focus on reducing antisocial behavior, may be able to reduce rehospitalization, arrests, and time in jail, as well as lower rates of both symptoms and aggressive behavior (Cuddeback, Morrissey, & Cusack, 2008;Hodgins et al, 2007b), although more research on their effectiveness is needed.…”
Section: Treatment Implicationsmentioning
confidence: 98%
See 1 more Smart Citation